Rancang Program Sistem Pemadam Kebakaran Berbasis Programable Logic Controller Smart Relay Type SR3B261BD - Leily W Johar; Fadli Eka Yandra; H NJ Thamrin; Umar Djufri; Rozlinda Dewi (Universitas Batanghari Jambi, 2022)
Programmable logic controller (PLC) can be programmed for various purposes, one of which is to design a fire extinguishing system, by assembling several components of PLC, solenoid, springkle, powersupply ,adapter ,smokedetector, heatdetector, pilotlamp, pushbutton, relay, selector switch. design the program settings to detect smoke and high temperatures that occur in the event of a fire. if the sensor detects smoke and high temperature, the sensor will give a signal to the plc to turn on and activate all working components and extinguish the fire.